Human immunodeficiency virus can infect the apical and basolateral surfaces of human colonic epithelial cells. - Fantini, J (1991)
The gastrointestinal tract is considered to be a major route of infection for the human immunodeficiency virus (HIV). To understand the interaction of HIV with epithelial cells of the intestinal mucosa, we have studied the infection of a human colon cancer cell clone HT-29-D4. The enterocyte-like differentiation of this clone can be modulated in vitro according to the concentration of glucose. We show that: (i) undifferentiated HT-29-D4 cells can be infected by HIV types 1 and 2 (HIV-1 and HIV-2) strains with no subsequent effect on cell growth; (ii) undifferentiated HT-29-D4 cells express a CD4-related antigen bearing epitopes of the immunoglobulin-like variable (V) region domains V1 and V2 of CD4 but lacking the epitope known to be involved in HIV envelope recognition; (iii) differentiated HT-29-D4 cells can be infected by HIV after an interaction with either the apical brush border membrane (luminal side) or the basolateral side (serosal side); (iv) the CD4-like molecule is restricted to the basolateral domain of differentiated cells; and (v) the infection is not inhibited by anti-CD4 monoclonal antibodies (mAbs) OKT4, OKT4A, Leu-3a, Bl4, 13-B-8-2, S-T4 or S-T40. We conclude that epithelial intestinal cells may represent a major site of entry for HIV. Infection of these epithelial cells may occur via the basolateral membrane by HIV-bearing lymphocytes or macrophages of the lamina propria and via the apical membrane by HIV present in the bowel lumen. This infection may remain silent for up to 9 months, and the virus can be rescued by cocultivation with lymphoid cells. These data may give an explanation for the long latent seronegative state that may occur in a HIV-infected individual.